PHARMACOLOGIST’S VIEW OF THE NEW CORONA VIRUS - Igić, Prof. dr Rajko (Scripta Medica, 2020)
To the editor, Despite many advances in the prevention and treatment of infectious diseases, the global spread of infections is accelerated by close contact among concentrated populations. A pandemic caused by a new type of coronavirus (SARS-CoV-2) continues to spread across the globe. This new disease attributed to COVID-19 emerged a century after the Spanish flu pandemic, which affected one-third of the world’s population, killing more than 50 million people.1 The disease, caused by the H1N1 virus, has been around for less than two years and it is still unclear what contributed to its termination; possibly a mutation of the virus reduced its viral strength. Since information about biological sciences and human medicine is far more advanced today than at the beginning of the 20th century, it is expected that the current pandemic will be contained, regardless of the potential for viral mutation. Scientists and doctors now face an urgent task - how to treat numerous sick people and stop the spread of this infection. The pandemic urgently requires identification of preventive measures, along with optimum means of diagnosis and treatment and data on dissemination of the infection, duration of incubation, clinical features of the disease, along with the best means of diagnosis and treatment for a very large number of people, and ultimately the long lasting consequences of the disease. In addition, we must identify pathways for the spread of the virus, its persistence on various surfaces and means of its inactivation.2